Systematics of Streptomyces Associated with the Alimentary Canal of Estuarine Fish and Shellfish of India - K., Dhevendaran; K., Annie (Fishery Technology, 2025)
Systematics of five Streptomyces strains isolated from fish and shellfish revealed the predominance of Genus, Streptomyces. Majority of them was grouped under gray colour series. Strains having rectiflexibiles of sporophore morphology were identified. Smooth walled spores were maximum in number. Isolates showed variations in requirement of sodium chloride for their growth. The bioactive compounds produced by them inhibited fish pathogen. Vibrio angiiillarum and human pathogens such as Aspergillns niger and Staphylococcus aureus. All the five strams of Streptomyces deviated from type strains and formed new taxa.